The Nature of the Notary as a Mediator in the Settlement of Disputes Between Parties - Aqmadea Eshafia, Shella; Masykur, M. Hamidi; Susilo, Hariyanto (The Islamic Education and Multiculturalism Foundation, 2024)
The position of notary as a mediator in its application does not contradict the law against religious norms, decency or suitability that can cause the honor and dignity of the notary position. Apart from that, the authority of a notary to resolve disputes through mediation and act as a mediator is not regulated in the provisions of the UUJN or related regulations, so that in this case there is a legal vacuum (rechtsvacuum) which has an impact on the absence of legal certainty for notaries in carrying out their duties to become mediators and resolve disputes outside the court. Therefore, a clear regulation is needed for notaries to carry out their duties and positions as mediators. The research method that will be used in this research is a type of normative juridical research, according to Ishaq, normative juridical research essentially examines the law conceptualized as norms or rules that apply in society, and become a reference for the behavior of everyone, this type of research is also called library research, theoretical / dogmatic research. Briefly related to the conclusions obtained by the author that although Article 15 and Article 17 of the UUJN do not explicitly prohibit notaries from acting as mediators, many notaries act as mediators based on the agreement of the parties to the dispute. This role provides an opportunity for notaries to be involved in dispute resolution by making a deed of peace that reinforces the results of the mediation